G117(P) Evaluation of the use of antenatal magnesium sulphate prior to in-utero transfer. (12th March 2018) - Shaw, A; Talbot, H
Abstract : Aim: To evaluate the regional use of antenatal magnesium sulphate prior to in-utero transfer (IUT) and establish whether this presents an opportune time to target improvement. Background: Premature delivery causes an increased risk of neurodevelopmental disability, accounting for long-term morbidity and reduced quality of life. Evidence demonstrates administering magnesium sulphate in threatened preterm labour reduces risk. In 2009, a Cochrane Review showed a significantly lower outcome of cerebral palsy (RR 0.68, 95% CI: 0.54 to 0.87). Magnesium sulphate is indicated for delivery expected within 24 hours and gestation between 24 +0 /40 to 29 +6 /40. Use can be considered until 33 +6 /40. Recent data from the National Neonatal Audit Programme (NNAP) suggests use varies according to level of care but did not differentiate dependent on those transferred in. Method: IUT requests are coordinated by the regional transport team. Information was retrospectively reviewed from 01/11/16 to 31/12/16, just after starting collection on magnesium sulphate use. Comparison was made from 01/03/17 to 30/04/17. Gestation, base hospital, risk of preterm delivery and maternal history was also recorded. Results: 189 cases were reviewed, 104 in 2016 and 85 in 2017. 35 were ineligible since gestation was >34 +0 /40. 9.2% patients had no information recorded. In 2016, 8.5% referrals received magnesium sulphate (5/59). This increased to 11.7% in 2017 (8/68). Only one patient was >30 +0 /40. Twenty neonatal units featured, two from out-of-region. The greatest use was at a level 2 unit (43%). 50% units recorded no use. Most referrals followed rupture of membranes associated with contractions. Conclusion: Magnesium sulphate has clear benefit in the preterm population but appears to be under-utilised in our region. The majority of women met the criteria for magnesium but had not received it. Findings amongst the IUT group are below those reported by NNAP. Condition was only sought at the time of referral. Recommendation: Increased recognition of national guidance is required alongside inter-collaborative working with obstetric teams. Results have been disseminated at the network meeting and a guideline is in progress. The transport service may offer a unique opportunity to prompt use in this potentially vulnerable group.